The relationship of some physical indicators (PMG, IMC) with indicators of physical fitness related to health - laloui, Abdelhafid; saghi , abdelkader; hamadi, djamel (sports creativity, 2023)
This study aims to find out the relationship of some physical indicators (PMG, IMC) with indicators of physical fitness related to health, where the researchers conducted a descriptive study. The researchers concluded that there is a negative relationship between the body mass index (IMC) and the level of health-related fitness indicators for male and female students, and there is a negative relationship between the body fat percentage index (PMG) and the level of health-related fitness indicators for male and female students. Keywords: Physical indicators, fitness, health.